Sexting is not always wanted: consequences on satisfaction and the role of sexual coercion and online sexual victimization - Garrido-Macías, Marta; Herrera, Antonio; Alonso-Ferres, María; Herrera, M. Carmen (Anales de Psicología / Annals of Psychology, 2023)
The understanding of sexting as a new form of interpersonal communication is increasing; however, little is known about whether the incidence, correlates, and outcomes of sexting vary depending on whether such behavior is done willingly or not. In this non-experimental study, we aimed to investigate the prevalence, predictors, and consequences of sexting among 310 Spanish young adults, who completed an online survey regarding their previous experiences of wanted and unwanted sexting behaviors, their sexual coercion and online sexual victimization experiences, and their levels of sexual and life satisfaction. The results showed that more than half and one third of the sample had been involved in wanted and unwanted sexting behaviors, respectively. Additionally, sexual coercion and online sexual victimization predicted a higher probability of engaging in unwanted sexual behaviors and, with that, a decrease of life satisfaction. Finally, having experienced more instances of sexual coercion was associated with lower life satisfaction by increasing the likelihood of suffering online sexual victimization experiences and engaging in additional unwanted sexting behaviors. Our findings show the importance of discerning between wanted and unwanted sexting and how doing so differently conditions the predictors and consequences of this phenomena.